The tyranny of merit : what's become of the common good? - Sandel, Michael J. (Farrar, Straus and Giroux, 2020)
"A world-famous political philosopher, and the bestselling author of Justice, reveals the driving force behind the resurgence of populism: the tyranny of the meritocracy and the resentments it produces"--